Cine-scapes : cinematic spaces in architecture and cities - Koeck, Richard, 1969- 4 0 16; 5 (New York : Routledge, 2013)
Cine-scapes explores the relationship between urban space, architecture and the moving image. While an impressive amount of research has been done with regards to the study of architecture portrayed in film, this book will offer a new perspective. There is little doubt that film can 'reflect' a postmodern condition, however, what this book demonstrates is that the postmodern, architectural condition in which we live is in fundamental terms filmic. We daily engage with spaces and places that are essentially cine-tectural. Drawing on the author's knowledge derived from architectural and film practice, Cine-scapes will: offer insight into architecture and urban debates through the eyes of a practitioner working in both fields - film and architectural design emphasise how cine-tectural tendencies are taking place or finding their way into urban practices can be used as a tool for educators, students and practitioners in architecture and urban design to communicate and discuss design issues with regard to contemporary architecture and cities. Cine-scapes ignites new ways of seeing, thinking and debating the nature of architecture and urban spaces--
Film, Mind and Body. Tectonics of Film Space -- City in our Mind -- Existential and Experiential Notions of Space -- Cinema, Architecture and the Everyday. Spatial Editing -- A Shared Space -- Architecture and Urban Form as Cinematic Apparatus -- Urbanity and Image. Urban Product Advertisement -- Place Marketing: Urban Architecture as Image -- Film Advertisement and Urban Spaces -- Conclusion: The Near Future of Cinescapes.
Includes bibliographical references (pages 188-206) and indexes.
Keywords: 2 -- 0; 6; Psychological aspects.;Psychological aspects.;Study and teaching. -- Space (Architecture);Motion pictures and architecture.;Cities and towns;Architecture;Architecture.; 20; 2